The Combination of Rituximab and Bendamustine as First-Line Treatment Is Highly Effective in the Eradicating Minimal Residual Disease in Follicular Lymphoma: An Italian Retrospective Study - Galimberti, Sara; Ciabatti, Elena; Ercolano, Giacomo; Grassi, Susanna; Guerrini, Francesca; Cecconi, Nadia; Rousseau, Martina; Cervetti, Giulia; Mazziotta, Francesco; Iovino, Lorenzo; Falzetti, Franca; Falcinelli, Flavio; et al. (Frontiers in Pharmacology, 2017)
R-Bendamustine is an effective treatment for follicular lymphoma (FL). Previous large trials demonstrated the prognostic role of the molecular minimal residual disease (MRD) during the most frequently adopted chemotherapeutic regimens, but there are not yet conclusive data about the effect of combination of rituximab (R) and bendamustine in terms of MRD clearance. Thus, the aim of this retrospective study was to assess if and in what extent the combination of rituximab and bendamustine would exert a significant reduction of the molecular disease in 48 previously untreated FL patients. The molecular marker at baseline was found in the 62.5% of cases; no significant differences were observed between patients with or without the molecular marker in respect of the main clinical features. Moreover, the quantization of the baseline molecular tumor burden showed a great variability: the median value was 1.4x10-2 copies, ranging from 3x10-5 to 4x104. The initial molecular tumor burden did not correlate with clinical features and did not impact on the subsequent quality of response. After treatment, 93% of cases became MRD-negative; the median reduction of the BCL2/JH load was 4 logs. The 2-years PFS was 85%; it was significantly longer for patients in complete than for those in partial response (91% vs 57%; p=0.002), and for cases with lower FLIPI-2 score (88% vs 60%; p=0.004). On the contrary, PFS did not differ between patients with or without the molecular marker at baseline; a molecular tumor burden 15 times higher was observed in the relapsed subgroup in comparison to the relapse-free one, but this difference did not change the PFS length. The 2-years OS was 93.6%; the only variable that significantly impacted on it was the FLIPI-2 score; the presence of the molecular marker at baseline or its behavior after treatment did not impact on survival. This study, even if retrospective and conducted on a small series of patients, would represent a proof of concept that R-bendamustine is able to so efficaciously eradicate MRD that it could be able to by-pass the prognostic significance of MRD already demonstrated for other chemotherapeutic regimens in follicular lymphoma.